Whole genome DNA methylation patterns in tissue and cfDNA associated with fibrosis reflect the complex signature of MASLD - Jongseong Ahn; Soyeon Kim; Jae Yoon Jeong; Sunghoon Heo; Kyung-hee Pyo; Eun-Ae Shin; Wonsik Kim; Jae-Ho Lee; Na Ryung Choi; Han Ah Lee; Hwang-Phill Kim; Sang-Hyun Song; et al. (PLoS ONE, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) can progress to steatohepatitis, being associated with inflammation, fibrosis, and immune cell interactions. Recent studies have reported an association between DNA methylation (DNAm) and MASLD. However, the relationship between DNAm and MASLD-related fibrosis is limited to liver tissue alone or focused on particular CpG sites. Moreover, despite the widely recognized sex differences in MASLD, studies that account for this variable remain limited. We performed whole-genome methylation sequencing (WGMS) on liver tissue and cell-free DNA (cfDNA) from patients with MASLD to investigate the association between fibrosis and DNAm. After initial filtering, the tissue and cfDNA data were further grouped by sex, and DNAm sites exceeding the minimum threshold for association with fibrosis were selected. Pathway analysis based on the genomic locations of CpG bins revealed both overlapping and distinct MASLD- and fibrosis-associated pathways across tissue and cfDNA, between males and females, and between intragenic and intergenic regions. Hepatic tissue deconvolution indicated the presence of immune cells and confirmed an increase in liver-derived cfDNA associated with fibrosis in cfDNA samples. Our study demonstrates the potential of WGMS as a platform for comprehensively observing the complex patterns of MASLD alterations.